Firm’s Characteristics, Corporate Governance Quality and Corporate Social Responsibility Disclosure - Mukhtaruddin Mukhtaruddin; Yulia Saftiana; Pandu Arya Dwikatama (Faculty of Economics, Universitas Sriwijaya, 2018)
Corporate Social Responsibility (CSR) has been internationally implemented in business activity. It is proven by many international standards, which had been issued and adopted by several companies. Implementation of CSR in Indonesia has been regulated in regulations number 40 year of 2007, however that regulation does not regulate any quantities of CSR that companies must do. This study attempts to investigate effect of company characteristics (company size (SIZE), company age (AGE), and profitability (PRO)), Good Corporate Covernance (GCG) are proxied by board of commissioner quality (BCQ) and audit committee quaality (ACQ) on CSR disclosure (CSRD). The samples are 25 mining companies listed in Indonesia Stock Exchange (IDX) period 2011 – 2013 and the company has reported their social responsibility in annual reports. The sample was selected by using of purposive sampling technique. Results indicate that BCQ has significant influence on CSRD. However, SIZE, AGE, PRO and ACQ found to have no effect on CSRD.